Design and Development of Novel 2-(Morpholinyl)-N-substituted Phenylquinazolin-4-amines as Selective COX-II Inhibitor - Dravyakar, Bhushan R.; Khedekar, Pramod B.; Khan, Tabassum; Sherje, Atul P.; Patel, Kavit N.; Suvarna, Vasanti (Anti-Inflammatory & Anti-Allergy Agents in Medicinal Chemistry, 2019)
Background: A novel series of 2-(Morpholin-4-yl)-N-phenylquinazolin-4- amine derivatives were synthesized and confirmed with spectral and elemental techniques. Methods: The compounds were tested for analgesic and anti-inflammatory activity by various pain models in rodents whereas the selectivity towards COX-2 receptor is determined by in vitro assay. Results: Screening results of compounds exhibited comparable biological activity with that of standard compound Indomethacin used for study. Compound 5d was found to be significantly potent with respect to its anti-inflammatory and analgesic activity with substantial COX-II selectivity. Conclusion: In silico analysis by molecular docking and 3D-QSAR studies justifies activity profile of compound 5d, suggesting that it may have potential for further evaluation and development as lead molecule for therapy in pain management.
Keywords: quinazoline